ASSESSMENT OF PAYMENT SYSTEMS ON THE PROPOSITION THAT COSTS AND RISKS OUTWEIGH BENEFITS TO USERS, BANKS AND SOCIETY - CLEMENT IKENNA OKEKE (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE & MANAGEMENT, 2014)
To support the successful implementation of cashless policy of Central Bank of Nigeria (CBN), through massive acceptance of e-payment, the study examined the proposition that the costs and risks of e-payment outweigh its benefits to users, banks and society. The assumption of the study was that if the benefits of e- payment outweigh its costs and risks to users, banks and society over other payment systems, then it will be easy to convince individuals and corporates to accept and prefer it. A questionnaire seeking to establish the extent to which the different payment systems perform on the basis of costs and risks outweighing benefits to users, banks and society, was administered on 282 highly educated and financially active users of the three payment systems based on their experiences in Nigeria. Using the data analyzed, the research questions were answered and the following findings made: compared to cash and cheque payment systems, e- payment was rated better to users, banks and society on the proposition that costs and risks outweigh benefits. The study concluded therefore that individuals, banks and society will accept and prefer e-payment platforms in their financial transactions. To sustain this conclusion the study made the following recommendations: Communicate the benefits of e-payment to customers, banks and the society; reduce the costs and risks of e- payment; and persuade on the superiority and acceptance of e-payment in spite of its costs and risks.